Computer assisted surgery, preoperative planning and navigation for pancreatic cancer. Issue 4 (12th February 2014) - Abe, Yuta; Itano, Osamu; Kitago, Minoru; Shinoda, Masahiro; Yagi, Hiroshi; Hibi, Taizo; Takano, Kiminori; Chiba, Naokazu; Kawachi, Shigeyuki; Shimazu, Motohide; Kitagawa, Yuko
Abstract Currently, the best treatment for locally advanced pancreatic cancer is considered to be safe and effective surgery, followed by appropriate additional therapies implemented as quickly as possible. The use of diagnostic imaging to assist surgery is being researched in a range of institutions. This report introduces the results of a study into the optimized contrast conditions for computed tomography (CT)‐volume rendering image generation, effective in providing image support for pancreatic surgery, and introduces actual cases in which imaging support was used in surgery. The authors demonstrated that the conventional contrast protocols used in making a diagnosis are not necessarily the optimum protocols for image creation. It is thought that the use of image‐supported surgery will improve the safety and effectiveness of pancreatic surgery.